The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmars.2021.596126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrient Management Scenarios on Marine Eutrophication Indicators: A Pan-European, Multi-Model Assessment in Support of the Marine Strategy Framework Directive

Abstract: A novel pan-European marine model ensemble was established, covering nearly all seas under the regulation of the Marine Strategy Framework Directive (MSFD), with the aim of providing a consistent assessment of the potential impacts of riverine nutrient reduction scenarios on marine eutrophication indicators. For each sea region, up to five coupled biogeochemical models from institutes all over Europe were brought together for the first time. All model systems followed a harmonised scenario approach and ran two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 87 publications
1
21
0
Order By: Relevance
“…For species diversity (D4C1), no clear responses were observed at a regional or sub-regional scale, except in the Baltic Sea with a slight increase and in the North-East Adriatic Sea with a decrease in diversity. The Baltic Proper was the only area that showed a slight increase in the two food-web criteria compared to the reference scenario; this might be related to the highly eutrophic nature of this ecosystem and the fact that a reduction of nutrient inputs might lead to an improvement of the marine environment e.g., better bottom oxygen levels, as observed in Saraiva et al (2019) and Friedland et al (2021), and thus better spawning conditions, leading to an increase in the Eastern Baltic cod stock. This response was not observed in other ecosystems that are also considered to be eutrophic such as the North-East Adriatic Sea, the Black Sea and the whole Adriatic Sea (from the JRC model) where nutrients reduction, mainly from the Po and Danube rivers, would reduce the assessed D3 and D4 criteria (Figure 2).…”
Section: Mean Change In Msfd Criteria and Tl Indicatorsmentioning
confidence: 95%
See 4 more Smart Citations
“…For species diversity (D4C1), no clear responses were observed at a regional or sub-regional scale, except in the Baltic Sea with a slight increase and in the North-East Adriatic Sea with a decrease in diversity. The Baltic Proper was the only area that showed a slight increase in the two food-web criteria compared to the reference scenario; this might be related to the highly eutrophic nature of this ecosystem and the fact that a reduction of nutrient inputs might lead to an improvement of the marine environment e.g., better bottom oxygen levels, as observed in Saraiva et al (2019) and Friedland et al (2021), and thus better spawning conditions, leading to an increase in the Eastern Baltic cod stock. This response was not observed in other ecosystems that are also considered to be eutrophic such as the North-East Adriatic Sea, the Black Sea and the whole Adriatic Sea (from the JRC model) where nutrients reduction, mainly from the Po and Danube rivers, would reduce the assessed D3 and D4 criteria (Figure 2).…”
Section: Mean Change In Msfd Criteria and Tl Indicatorsmentioning
confidence: 95%
“…Thus, limiting the simulations to 8 years could have impeded a clear cause-effect relationship. This limitation was also highlighted in the results of LTL modules (Friedland et al, 2021;Grizzetti et al, 2021) which showed that 8 years of simulations were not enough to reach a new equilibrium. The internal nutrient dynamics and long residence times hampered the effect of the nutrient input reductions in the assessed ecosystems.…”
Section: Mean Change In Msfd Criteria and Tl Indicatorsmentioning
confidence: 99%
See 3 more Smart Citations